2019
DOI: 10.19080/jaicm.2019.08.555743
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Outcome of Sepsis at Surgical ICU: A Prospective Multi-Center Prospective Study

Abstract: The current study supposed that early changes in serum levels of primary phase reactants and copeptin could predict the outcome of patients developed sepsis after admission to ICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
(28 reference statements)
1
1
0
Order By: Relevance
“…Among the participants in the current study, a considerable correlation was found between the increase in SOFA score and mortality. This discovery aligns with the outcomes documented by Salem et al [23] , wherein they illustrated that the mean SOFA score for survivors was 9.6±1.8, whereas it was 10.5±2.2 for non-survivors. Between the 2 groups, a statistically significant difference in SOFA scores was also noted (p=0.005), according to the study.…”
Section: Discussionsupporting
confidence: 90%
“…Among the participants in the current study, a considerable correlation was found between the increase in SOFA score and mortality. This discovery aligns with the outcomes documented by Salem et al [23] , wherein they illustrated that the mean SOFA score for survivors was 9.6±1.8, whereas it was 10.5±2.2 for non-survivors. Between the 2 groups, a statistically significant difference in SOFA scores was also noted (p=0.005), according to the study.…”
Section: Discussionsupporting
confidence: 90%
“…This agreed with Salem et al, who showed that APACHE II score was 22 ± 2.9 and 23.5 ±4 in survivors and non-survivors respectively with statistically significant difference between the two groups (p=0.005). The mean SOFA score was 9.6 ± 1.8 and 10.5 ± 2.2 in survivors and nonsurvivors respectively with statistically significant difference between the two groups ( p=0.005) [27] .…”
Section: Discussionmentioning
confidence: 87%